Aplicação superficial de calcário e diferentes resíduos em soja cultivada no sistema plantio direto - Corrêa, Juliano Corulli; Freitag, Elisa Eni [UNESP]; Büll, Leonardo Theodoro [UNESP]; Crusciol, Carlos Alexandre Costa [UNESP]; Fernandes, Dirceu Maximino [UNESP]; Marcelino, Rafael [UNESP] (Instituto Agronômico de Campinas, 2009)
A prática da correção da acidez do solo pela aplicação superficial de corretivos sobre a palha no sistema plantio direto se restringe ao calcário, não havendo maiores estudos em relação à escória de aciaria, lama cal e lodo de esgoto centrifugado. O objetivo do trabalho foi avaliar os índices de acidez do solo e a produtividade da soja em função da aplicação superficial de lodo de esgoto centrifugado, lama cal, escória de aciaria e calcário dolomítico. O trabalho foi desenvolvido em Latossolo Vermelho distrófico, durante os anos agrícolas de 2002 a 2005, sob sistema plantio direto. Os tratamentos constituíram da aplicação superficial de escória de aciaria (E), lama cal (Lcal), lodo de esgoto centrifugado (LC), calcário dolomítico e sem aplicação de corretivo, em delineamento em blocos ao acaso, com quatro repetições. A aplicação superficial de escória de aciaria, lama cal e lodo de esgoto centrifugado permite a correção da acidez do solo, o deslocamento do Ca2+, o aumento da saturação por bases e redução do Al3+ até 40 cm, e para o calcário, até 20 cm, fatores que condicionaram o aumento da produtividade da soja para os tratamentos LC, E e Lcal em 2003/2004 e 2004/2005 e para LC e E em 2002/2003 no sistema plantio direto.

The practice of correcting soil acidity by surface application of pH-correcting materials on crop residues in the no-till system is restricted to limestone. No further studies are available on the use of steel slag, lime mud, and centrifuged sewage sludge. The objective of this study was to evaluate soil acidity and yield of soybean as a function of surface application of centrifuged sewage sludge, lime mud, steel slag, and dolomitic limestone. The study was conducted on a dystrophic Clayey Rhodic Hapludox soil, during the 2002_2005 cropping seasons, under notill system. Treatments consisted on surface application of slag _ E, lime mud _ Lcal, centrifuged sewage sludge _ LC, dolomitic limestone, and zero application of correcting materials, conducted in a random block design with four replicates. Surface application of steel slag, lime mud, and centrifuged sewage sludge allowed soil acidity correction, Ca2+ displacement, increased base saturation, and Al3+ reduction down to 40cm depth, whereas for limestone those effects occurred down to 20 cm. The interaction among those factors promoted a soybean yield increase for the LC, E, Lcal, and limestone treatments in the 2003/04 and 2004/05 seasons, as well as for the LC and E treatments in the 2002/03 season, under the no-till system.
Surface application of limestone and different residues on soybean grown in no-till system
Keywords: Lodo de esgoto; escória de aciaria; lama cal; calcário; Sewage sludge; steel slag; lime mud; limestone